Design and development of multi-functional graphitic carbon nitride heterostructures embedded with copper and iron oxide nanoparticles as versatile sensing platforms for environmental and agricultural applications - Khasim, Syed; Pasha, Apsar; Dastager, Syed G.; Panneerselvam, Chellasamy; Hamdalla, Taymour A.; Al-Ghamdi, S. A.; Alfadhli, S.; Makandar, Mohammad Basha; Albalawi, Jalal Bassam; Darwish, A. A. A. (Ceramics International, 2023)
In the recent past, agrotechnology has witnessed a tremendous change due to the advent of technologies employed towards enhancing the yield and quality of the crops. The application of nanotechnology in agriculture is promoting sustainable practices and smart farming. Currently, nanomaterial-based sensors are gaining considerable attention in agrotechnology, such sensors can detect the environmental conditions and support for crop growth and enhances the agricultural yield. Graphiticcarbon nitride (g-C3N4), a soft polymer belongs to a class of 2-D semiconductors which are affordable, metal-free, indispensable for sensing applications due to significant changes in their conductivity upon exposure to analyte molecules in nano-regime. Further, this g-C3N4 can be combined with other nano metal oxides to form nanocomposites with remarkable properties and superior performance. In this work we report development of high-performance sensors based on graphitic carbon nitride embedded with copper and iron oxide nanoparticles. These heterostructures offers tremendous improvement in the physical and chemical properties due to the synergetic interactions between various phases. The chemiresistive sensor fabricated from these nanocomposites exhibit excellent sensitivity towards monitoring methane gas @ ppb level, relative humidity (% RH), and soil moisture content. Owing to their excellent sensitivity, stability and selectivity, this graphitic carbon nitride embedded with Cu and Fe oxide nanoparticles could be potentially used as multifunctional sensors towards environmental monitoring and greenhouse conditions in agricultural applications.
Keywords: Agricultural sensors; CuO nanoparticles; Environmental monitoring; FeO nanoparticles; Graphitic carbon nitride

Novel Biogenic Synthesis of Pd/TiO@BC as an electrocatalytic and possible energy storage materials - Khasim, Syed; Dastager, Syed G.; Alahmdi, Mohammed Issa; Hamdalla, Taymour A.; Panneerselvam, Chellasamy; Makandar, Mohammad Basha (Ceramics International, 2023)
The standard approach towards synthesizing nanomaterials exercising chemical or physical techniques generally costs more and necessitates using toxic chemicals, which negatively affect the environment. For the first time, an investigation of a basic green synthesis approach for Phyto fabrication of Pd/TiO@BC nanocomposite via biomass of rice husk (Oryza sativa L) is conducted to sustain the green chemistry for synthesis of less toxic chemicals. XRD analysis revealed that the structure of Phyto synthesized Pd/TiO@BC is crystalline, while UV, FTIR, SEM and EDX analyses marked the victorious nanocomposite biosynthesis. We have investigated the electrocatalytic and biomedical applications of the novel nanocomposite Pd/TiO@BC at different environmental conditions. Testing the potential electrochemical properties of Pd/TiO@BC to eliminate the Congo red (CR) dye from wastewater marked its high removal efficiency, which attained 90% owing to the higher electron efficiency. Its sensitivity for CR was also examined, and acceptable degradation activity was observed. These Pd/TiO@BC proved to be beneficial in various fields, including electrochemistry, catalysis sensors, wastewater treatment, and nano-devices, and in the transformation of hazardous particles into less harmful substances. Its great potential for use as a supercapacitor is promised by its feature, including durability and compact stability. Significant guidelines could be extracted from the results, which are helpful in material size, synthesis, selection, and configuration design for various energy storage gadgets. The synthesis of high performance and economical materials through green chemistry is a novel approach towards effective energy storage and alteration procedure operation.
Keywords: Electro catalytic; Energy storage; Oryza sativa L biochar; Pd; PdNPs and TiONPs; TiO@BC